PENGARUH KONDISI KEUANGAN, PERTUMBUHAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN WHOLESALE AND RETAIL TRADE DI BEI - JUNIARTO KUSWARDI, HANS (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Going concern audit opinion is an opinion issued by the auditor because there is doubt on the ability of an entity to continue to thrive. This opinion is beneficial to the stakeholders to avoid mistakes in investment. In giving the going concern audit opinion, the auditor must consider several factors that affect the provision of audit opinion. The purpose of this study was to test the impact of company's financial condition, growth, and the quality of audit towards going concern audit opinion giving. This research design was quantitative with a hypothesis. Dependent variable of this research is going concern audit opinion, while the independent variable are the company's financial condition that measured by the liquidity ratio, profitability, and the solvability ratio, the company's growth and audit quality. The Object of research were wholesale and retail trade companies registered in a row in Indonesia Stock Exchange from 2007-2010. Data analysis was performed using logistic regression. The analysis shows that the financial condition of the solvability ratio has a positive and significant impact on the provision of going concern audit opinion, while the financial condition of the liquidity ratios, profitability, and quality of audit don't have positive and significant impact while company's growth does not have a negative and significant impact on the provision of going concern audit opinion.